Facile synthesis and performance of Na-doped porous lithium-rich cathodes for lithium ion batteries. Issue 62 (14th June 2016) - Wang, Di; Liu, Meihong; Wang, Xianyou; Yu, Ruizhi; Wang, Gang; Ren, Qifang; Yang, Xiukang
Abstract : Na-doped porous lithium-rich (Li-rich) cathode microspheres (∼1 μm) were firstly prepared via the solvothermal method and subsequently a high-temperature calcination process. Abstract : Na-doped porous lithium-rich (Li-rich) cathode microspheres (∼1 μm) were firstly prepared via the solvothermal method and subsequently a high-temperature calcination process. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and nitrogen adsorption–desorption isotherms were used to characterize the structure and morphology of the as-prepared cathode material. It has been found that the as-prepared material has an obvious internal porous structure with the existence of 5 at% Na ions. Besides, the obtained cathode material possesses excellent electrochemical characteristics. For example, it can deliver a high initial discharge capacity of 305.2 mA h g −1 between 2.0 V and 4.6 V at a rate of 0.1C at room temperature and the retention of the capacity is still as high as 88.2% after 200 cycles. Furthermore, the electrochemical impedance spectroscopy (EIS) results also show that the introduction of Na ions can decrease the charge transfer resistance of the as-prepared cathode material. The excellent electrochemical performance of the as-prepared cathode material can probably be attributed to the improved stability of the bulk lattice and the expanded Li slab space, which facilitates lithium ion diffusion and effectively enhances the stability of the layered structure of the materials.